A potent broad-spectrum neutralizing antibody targeting a conserved region of the prefusion RSV F protein - Yongpeng Sun; Liqin Liu; Hongsheng Qiang; Hui Sun; Yichao Jiang; Luo Ren; Zemin Jiang; Siyu Lei; Li Chen; Yizhen Wang; Xue Lin; Guosong Wang; et al. (Nature Communications)
Abstract Respiratory syncytial virus (RSV) poses a significant public health challenge, especially among children. Although palivizumab and nirsevimab, neutralizing antibodies (nAbs) targeting the RSV F protein, have been used for prophylaxis, their limitations underscore the need for more effective alternatives. Herein, we present a potent and broad nAb, named 5B11, which exhibits nanogram level of unbiased neutralizing activities against both RSV-A and -B subgroups. Notably, 5B11 shows a ~20-fold increase in neutralizing efficacy compared to 1129 (the murine precursor of palivizumab) and approximately a 3-fold increase in neutralizing efficacy against B18537 in comparison to nirsevimab. Cryo-electron microscopy analysis reveals 5B11’s mechanism of action by targeting a highly conserved epitope within site V, offering a promising strategy with potentially lower risk of escape mutants. Antiviral testing in a female cotton rat model demonstrated that low-dose (1.5 mg/kg) administration of 5B11 achieved comparable prophylactic efficacy to that achieved by high-dose (15 mg/kg) of 1129. Furthermore, the humanized 5B11 showed a superior in vivo antiviral activity against B18537 infection compared to nirsevimab and palivizumab. Therefore, 5B11 is a promising RSV prophylactic candidate applicable to broad prevention of RSV infection.